Analysis of Bangka Culinary Business Development in Gading Serpong - Irene Illena; Budi Setiawan (Return : Study of Management, Economic and Bussines, 2023)
Gading Serpong area is developing into a center of business, lifestyle, health and education then office buildings, worship facilities, culinary centers to meet the needs of housing and investment for residents of the capital and its surroundings. The culinary business is currently a big business and attracts many people because they like culinary and want to try local food from other regions and has high profit potential. The Bangka Culinary Business in Gading Serpong with several existing stores has continued to grow since 2018 coupled with the occupancy and community around so that the need for a variety of foods has also increased. This research method uses qualitative methods. While the results of this research conducted by interviews that Bangka culinary first opened in 2017 through a shop because at that time there were no Bangka cuisine rivals in Gading Serpong. The development of Bangka's culinary business continues to grow rapidly from 2018 until now because many are in demand by various groups of people, and the results of these interviews also show the satisfaction of visitors who visit snack shops or restaurants is very satisfied, both from products, services, and management according to existing business standards.